ICT and teacher change: case study in a Hong Kong secondary school - Mo, Hoi Ling Stella. (2011)
The 21st century is considered an era of information explosion. Information and communication technology is developing fast and penetrating into everyone's life and daily living. Governments of countries all over the world have invested huge amounts of money into the development of ICT in teaching and learning over the past 20 years. The Hong Kong government, with no exception, has invested huge sums of money alongside the declaration of initiatives for implementing the use of ICT into teaching and learning. However, the progress is still lagging behind the expectation despite the money and human resources invested. The implementation involves not only the introduction of a tool in changing classroom practice and pedagogy, but also a paradigm shift. The complexity of change, as Fullan (2001) describes it, is far beyond people's expectations.